Powder Metallurgy: An Alternative for FeMnSiCrNi Shape Memory Alloys Processing - Pricop, Bogdan; Söyler, Ahmet U.; Özkal, Burak; Bujoreanu, Leandru G. (Frontiers in Materials, 2020)
In the case of quintenary Fe-Mn-Si-Cr-Ni shape memory alloys (SMAs), ingot metallurgy (IM) has technological shortcomings concerning compositional segregation, imperfect melt-incorporation of Si, demanganization during heating and cooling-induced cracking, which can be effectively surmounted by combining powder metallurgy (PM) with mechanical alloying (MA). The paper reviews the results reported in the processing and characterization of PM-MA’ed FeMnSiCrNi SMAs, with special emphasis on the findings obtained by present authors in the last decade. Specimens with nominal chemical compositions Fe-18Mn-3Si-7Cr-4Ni and Fe-14Mn-6Si-9Cr-5Ni (mass %) were produced by IM and PM. In the latter case various volume fractions of as-blended powders were MA’ed under protective atmosphere, before being pressed and sintered. Further compacting, up to 5 % porosity degrees, was achieved by hot rolling. Structural analysis, performed by X-ray diffraction and scanning electron microscopy, revealed the formation of unusually large amounts of α’-body centred cubic (bcc) thermally induced martensite. This undesirable martensite seemed to be destabilized by tensile pre-straining, and enabled PM specimens to reach higher stresses than IM ones. The formation and accumulation of α’-bcc stress induced martensite was enhanced by tensile pre-straining, mechanical cycling and augmentation of MA’ed powder fraction. It has been argued that the optimization of technological processing parameters of heat treatment (HT) and hot rolling (HR) combined with MA’ed powder fraction caused the augmentation of shape memory effect (SME) magnitude. DMA-temperature scans revealed an increasing tendency of internal friction (tan δ) with MA’ed powder fraction, as well as the presence of two tan δ maxima ascribed to antiferromagnetic-paramagnetic transition and martensite reversion to austenite, respectively. DMA-strain sweeps emphasized the occurrence of a plateau on the storage modulus vs. strain amplitude variation which was associated with stress-induced formation of ε hexagonal close-packed (hcp)-martensite. In spite of large α’-bcc amounts, PM-MA’ed Fe-14Mn-6Si-9Cr-5Ni experienced free-recovery SME which was enhanced by thermomechanical training. Coupling rings, meant to connect vibrating pipes that transport turbulent fluids, being able to mitigate vibrations that could accidentally open the connection, were manufactured and tested.